2012
DOI: 10.1371/journal.pone.0033626
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Ameliorates Kidney Fibrosis by Inhibiting the Activation of mTOR Signaling in Interstitial Macrophages and Myofibroblasts

Abstract: Interstitial fibrosis is an inevitable outcome of all kinds of progressive chronic kidney disease (CKD). Emerging data indicate that rapamycin can ameliorate kidney fibrosis by reducing the interstitial infiltrates and accumulation of extra cellular matrix (ECM). However, the cellular mechanism that regulates those changes has not been well understood yet. In this study, we revealed the persistent activation of mammalian target of rapamycin (mTOR) signaling in the interstitial macrophages and myofibroblasts, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 38 publications
6
110
0
Order By: Relevance
“…Other signaling molecules, including suppressor of cytokine signaling 3 (SOCS3) and IKK, have also been reported to be upregulated in kidney M⌽ in nephritis (4,53). Recently, it was reported that kidney M⌽ in UUO highly express mTOR signaling and that rapamycin inhibited inflammatory activity of M⌽ via mTOR signaling (10). However, the signaling pathways involved in M2 M⌽ function in kidney disease remain unclear.…”
Section: Frontiers Of Kidney Macrophage Researchmentioning
confidence: 99%
“…Other signaling molecules, including suppressor of cytokine signaling 3 (SOCS3) and IKK, have also been reported to be upregulated in kidney M⌽ in nephritis (4,53). Recently, it was reported that kidney M⌽ in UUO highly express mTOR signaling and that rapamycin inhibited inflammatory activity of M⌽ via mTOR signaling (10). However, the signaling pathways involved in M2 M⌽ function in kidney disease remain unclear.…”
Section: Frontiers Of Kidney Macrophage Researchmentioning
confidence: 99%
“…On the other hand, myostatin (MSTN), which is secreted by muscle, inhibits myogenesis 21 and muscle hypertrophy [22][23][24] (via regulation of mammalian target of rapamycin [MTOR]) but promotes fibrosis 25,26 and adipogenesis 21 . An animal model of rotator cuff injury has also shown that MTOR modulates fatty infiltration 27 , and it regulates fibrosis [28][29][30] . Growth factors such as transforming growth factor b1 (TGFB1) and connective tissue growth factor (CTGF) are considered master regulators of fibrosis, which in simple terms represents an imbalance between the breakdown of extracellular matrix proteins by matrix metalloproteinases (MMPs) and the activity of tissue inhibitors of metalloproteinase (TIMPs), which inhibit MMPs 31 .…”
mentioning
confidence: 99%
“…This finding differs from our data. The relationship between P311 and TGF-β1 might be reasonable to explain this discrepancy, because infiltration of inflammatory cells is an early and characteristic feature of renal fibrosis (37). During renal fibrosis, at early stages of repair with abundant inflammatory cells, the antifibrogenic effect of P311 may be offset by TGF-β1 and exhibit a pro-fibrogenic effect, while at advanced stages of repair while inflammatory cells gradually disappeared, the antifibrogenic effect of P311 may increase over time and become maximal toward the end of the reparative process (18).…”
Section: Discussionmentioning
confidence: 99%